HALAL KOPITIAM CHOICES AMONG YOUNG MUSLIM CONSUMERS IN NORTHERN REGION OF PENINSULAR MALAYSIA - Ismalaili Ismail; Nik Azlina Nik Abdullah; Syazwani Ya; Rozihana Sheikh Zain; Noor Asyikin Mohd Noor (Journal of Islamic, Social, Economics and Development, 2019)
Recently, there is an increasing statistic towards Halal industry which 60 percent of the annual global market value is generated from Halal food business including Halal kopitiam and restaurants. Halal defined as permissible and lawful according to Quran and Sharia. In Malaysian context, food producers such as Halal kopitiam are compulsory to follow the standards set by JAKIM and Islamic law in handling their food preparation. Additionally, the Halal kopitiam need to display their Halal certificate and logo in their premises. The main objective of this study is to examine the factors influencing Halal kopitiam choices among young Muslim consumers. A set of questionnaires were administered to 357 young Muslim consumers in northern region namely Perlis, Kedah, Penang and Perak. The results of this study suggested two variables which are attitude and ambience were significantly related to Halal kopitiam choices among young Muslim consumers, while trust was not significantly related to Halal kopitiam choices. The finding of this study may be beneficial to marketers and Halal food producers such as kopitiam and restaurants in Malaysia to understand Halal kopitiam choices among young Muslim consumers as well as to maintain an ethical consideration in their food business activities related to Halal concept.